Uv-curable adhesive composition, adhesive film comprising the same, polarizing film comprising the same, and display device including the polarizing film
Patent Information
- Application Number
- CN202280015093.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-05
- Filing Date
- 2022-10-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-10-25
AI Technical Summary
In the prior art, the adhesives used for polarizing plates cannot simultaneously exhibit good bonding strength on both moisture-permeable and moisture-impermeable substrates, which necessitates the replacement of the adhesives separately, increasing costs and reducing productivity.
A UV-curable adhesive composition is used, comprising monofunctional acrylates, polyfunctional acrylates, silane coupling agents, cationic initiators, and photosensitizers. The silane coupling agents contain epoxy groups and are used to prepare the adhesive layer of the polarizing film to accommodate different types of protective substrates.
It achieves excellent adhesion strength and wetting properties on both permeable and impermeable substrates, reduces the frequency of adhesive replacement, and improves production efficiency and the appearance quality of the adhesive layer.
Smart Images

Figure CN117043296B_ABST
Abstract
Description
Technical Field
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2021-0151166, filed with the Korean Intellectual Property Office on November 5, 2021, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a UV-curable adhesive composition, an adhesive film comprising the same, a polarizing film comprising the same, and a display device comprising the polarizing film. Background Technology
[0003] Recently, with the development of optical technologies as a stepping stone, various types of display devices, such as plasma display panels (PDPs), liquid crystal displays (LCDs), and organic light-emitting diodes (OLEDs), have been proposed and marketed to replace conventional cathode ray tubes. Recently, the characteristics required for these display devices have become more demanding, and correspondingly, the requirements for the characteristics of peripheral components used in these display devices, such as optical films and polarizing films, have also become more stringent.
[0004] Liquid crystal displays (LCDs) are used in various display devices, such as televisions, mobile phones, car navigation systems, portable gaming devices, and other portable terminals, by utilizing features such as low power consumption, low voltage operation, light weight, and thinness. These LCDs can include Vertical Alignment (VA) mode, In-Plane Switching (IPS) mode, Edge Field Switching (FFS) mode, and Optically Compensated Curve (OCB) mode. These LCDs typically consist of a backlight, liquid crystal cells containing liquid crystal molecules sandwiched between two electrodes, and two polarizing plates positioned on either side of the liquid crystal cells. When a voltage is applied, the transmitted light can be controlled by changing the optical refractive index of the liquid crystal molecules to display an image. Furthermore, in these modes, the light absorption axes of the two polarizing films are arranged at 90° relative to each other, so that no light is transmitted when no voltage is applied to the liquid crystal cells. LCDs that display black when no voltage is applied and white when voltage is applied are called normally black type.
[0005] Recently, the polarizing plate market has focused on minimizing defects and improving product productivity. In related technologies, triacetyl cellulose (TAC) has been used as a protective material for polarizing plates (with a moisture-permeable substrate (WVRT>200g / m³)). 2 Water-based adhesives are used to manufacture polarizing plates, but currently, moisture-impermeable substrates (WVRT < 200 g / m²) are mainly used. 2 (e.g., PET, acrylic, or COP film)
[0006] When using a conventional moisture-permeable protective substrate, the upper / lower protective substrate of the polarizing plate can be attached with one type of adhesive. However, in recent years, in product groups that use both moisture-permeable and non-moisture-permeable substrates instead of just a moisture-permeable substrate, the problem is that it is difficult to achieve sufficient bond strength by using only a water-based adhesive.
[0007] In other words, an adhesive composition that exhibits good adhesive strength to a moisture-permeable protective substrate is disadvantageous in terms of adhesive strength to an impermeable substrate, and vice versa. Therefore, since the properties of the substrate are applied differently, the adhesive cannot be changed according to the substrate. Thus, it is necessary to research adhesives that can be applied to both moisture-permeable and impermeable substrates by increasing the adhesive strength margin.
[0008] Currently, to address this issue, adhesives are typically applied to the upper and lower surfaces of the polarizing plate, respectively, depending on whether the substrate is permeable or impermeable. While the advantage is increased adhesive strength when the adhesive is applied to both permeable and impermeable substrates, the problem is that the adhesive needs to be changed each time depending on the product group, leading to increased costs and reduced production productivity.
[0009] When the adhesive applied to the polarizing film is replaced, there is usually a period of inactivity of about 3 to 6 hours. Therefore, additional time is required for path changes due to wet / dry changes, adhesive discharge / filling, screen roller replacement, pipe cleaning / rinsing, etc.
[0010] Therefore, it is necessary to develop an adhesive layer for use on polarizing plates that can be used according to the product group currently being applied, regardless of the type of protective substrate (moisture-permeable substrate and moisture-impermeable substrate) to which the polarizing plate is attached.
[0011] [Primary Technology]
[0012] Japanese Patent Registration No. 6536022 Summary of the Invention
[0013] Technical issues
[0014] The present invention relates to a UV-curable adhesive composition, an adhesive film comprising the same, a polarizing film comprising the same, and a display device comprising the polarizing film.
[0015] Technical solution
[0016] According to an exemplary embodiment of the present invention, a UV-curable adhesive composition is provided, comprising: a monofunctional acrylate; a polyfunctional acrylate; a silane coupling agent; a cationic initiator; and a photosensitizer, wherein based on 100 parts by weight of a monomer comprising the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, the silane coupling agent is included in an amount of 15 parts by weight or more, and the polyfunctional acrylate comprises acrylates having two functional groups and acrylates having three or more functional groups, wherein based on 100 parts by weight of the polyfunctional acrylate, the acrylate having two functional groups is included in an amount of 70 parts by weight or more, and the silane coupling agent has one or more epoxy groups in the molecule, wherein at least one of the epoxy groups is an alicyclic epoxy group or a non-alicyclic epoxy group.
[0017] According to another exemplary embodiment of the present invention, an adhesive film is provided which comprises a UV-curable adhesive composition or a cured product thereof according to the present invention.
[0018] According to yet another exemplary embodiment, a polarizing film is provided, comprising: a polarizer; a first adhesive layer and a second adhesive layer disposed on two surfaces of the polarizer; and a layer disposed on the opposite surface of the first adhesive layer to the surface in contact with the polarizer and having a strength of 150 g / m². 2 • A transparent protective film with 24-hour or less moisture permeability; and a surface disposed on the opposite side of the polarizer contact surface of the second adhesive layer, having a moisture permeability of 150 g / m². 2 • A transparent protective film with 24-hour or greater moisture permeability, wherein the first adhesive layer and the second adhesive layer are adhesive films according to the present invention.
[0019] Finally, a display device comprising a polarizing film according to the present invention is provided.
[0020] Beneficial effects
[0021] According to an exemplary embodiment of the present invention, the UV-curable adhesive composition necessarily comprises a monofunctional acrylate; a polyfunctional acrylate; a silane coupling agent; a cationic initiator; and a photosensitizer. Specifically, based on 100 parts by weight of monomer, the silane coupling agent is included in an amount of 15 parts by weight or more, the silane coupling agent having one or more epoxy groups in its molecule, and at least one of said epoxy groups comprising an alicyclic epoxy group or a non-alicyclic epoxy group, thereby exhibiting excellent adhesive strength regardless of whether the substrate to be attached is moisture-permeable or moisture-impermeable.
[0022] Furthermore, since the multifunctional acrylates contained therein include two types of acrylates, and the acrylates with two functional groups contain specific amounts and specific functional groups, they improve the wetting properties of the polarizing plate or substrate and have excellent adhesive strength, regardless of the protective substrate used.
[0023] Furthermore, the UV-curable adhesive composition according to an exemplary embodiment of the present invention contains monofunctional and polyfunctional acrylates in specific amounts to reduce the surface energy of the adhesive layer containing the composition and has excellent wetting properties to the polarizer or substrate without causing bubbles during the process, thereby having excellent appearance quality of the polarizing film containing the composition. Attached Figure Description
[0024] Figure 1 A stacked structure of polarizing films according to an exemplary embodiment of the present invention is shown.
[0025] <Explanation of Figure Labels and Symbols>
[0026] 1: Moisture permeability is 150g / m² 2 • 24-hour or longer transparent protective film
[0027] 2: Second adhesive layer
[0028] 3: Polarizer
[0029] 4: First adhesive layer
[0030] 5: Moisture permeability is 150g / m² 2 • 24-hour or shorter transparent protective film Detailed Implementation
[0031] Before describing the present invention, some terms will be defined.
[0032] In this specification, unless explicitly stated otherwise, the words “comprising” and variations such as “including” or “containing” will be understood to mean including the stated elements but excluding any other elements.
[0033] In this specification, "p to q" means the range of "p or greater and q or less".
[0034] In this specification, acrylate means both acrylate and (meth)acrylate.
[0035] Examples of the invention will be described in detail below to enable those skilled in the art to readily implement it. However, the invention can be implemented in various different forms and is not limited to the embodiments described herein.
[0036] An exemplary embodiment of the present invention provides a UV-curable adhesive composition comprising: a monofunctional acrylate; a polyfunctional acrylate; a silane coupling agent; a cationic initiator; and a photosensitizer. Based on 100 parts by weight of a monomer comprising the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, the silane coupling agent is included in an amount of 15 parts by weight or more, and the polyfunctional acrylate comprises acrylates having two functional groups and acrylates having three or more functional groups. Furthermore, based on 100 parts by weight of the polyfunctional acrylate, the acrylate having two functional groups is included in an amount of 70 parts by weight or more, and the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups is an alicyclic epoxy group or a non-alicyclic epoxy group.
[0037] According to an exemplary embodiment of the present invention, the UV-curable adhesive composition necessarily comprises a monofunctional acrylate; a polyfunctional acrylate; a silane coupling agent; a cationic initiator; and a photosensitizer. Specifically, based on 100 parts by weight of monomer, the silane coupling agent is included in an amount of 15 parts by weight or more, the silane coupling agent having one or more epoxy groups in its molecule, and at least one of said epoxy groups comprising an alicyclic epoxy group or a non-alicyclic epoxy group, thereby exhibiting excellent adhesive strength regardless of whether the substrate to be attached is moisture-permeable or moisture-impermeable.
[0038] Each feature of the adhesive composition included in this invention will now be described.
[0039] In one exemplary embodiment of the present invention, the monofunctional acrylate may be an alkyl (meth)acrylate. In an alkyl (meth)acrylate, the alkyl group may be branched even in a straight chain, provided that the alkyl group has three or more carbon atoms. Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, etc. In addition, as monopolymerizable monomers, alkyl methacrylates having more carbon atoms in the alkyl group can be used, such as 2-ethylhexyl methacrylate; aralkyl methacrylates, such as benzyl methacrylate; terpene alcohol methacrylates, such as isobornyl methacrylate; methacrylates having a tetrahydrofurfuryl structure, such as tetrahydrofurfuryl methacrylate; methacrylates having a cycloalkyl group on the alkyl group, such as cyclohexyl methacrylate, dicyclopentyl acrylate, and 1,4-cyclohexanediethanol monoacrylate; aminoalkyl methacrylates, such as N,N-dimethylaminoethyl methacrylate; and methacrylates having an ether bond on the alcohol group, such as 2-phenoxyethyl methacrylate, ethyl carbitol methacrylate, and phenoxy polyethylene glycol methacrylate.
[0040] In addition, monofunctional (meth)acrylates having a hydroxyl group at the alcohol moiety or monofunctional (meth)acrylates having a carboxyl group at the alcohol moiety can also be used. Specific examples of monofunctional (meth)acrylates having a hydroxyl group at the alcohol moiety include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate or 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, trimethylolpropane mono(meth)acrylate, and pentaerythritol mono(meth)acrylate. Specific examples of monofunctional (meth)acrylates having a carboxyl group at the alcohol moiety include 2-carboxyethyl (meth)acrylate, 1-[2-(meth)acryloyloxyethyl]phthalate, 1-[2-(meth)acryloyloxyethyl]hexahydrophthalic acid, 1-[2-(meth)acryloyloxyethyl]succinic acid, 4-[2-(meth)acryloyloxyethyl]trimethic acid, etc.
[0041] In another exemplary embodiment, the monofunctional acrylate may be 4-hydroxybutyl acrylate (4-HBA).
[0042] Monofunctional acrylates refer to acrylates that have one functional group in their molecule, and the functional group can be an acrylate group.
[0043] In one exemplary embodiment of the present invention, a type of monofunctional acrylate may be used.
[0044] In one exemplary embodiment of the present invention, two types of monofunctional acrylates may be used.
[0045] In one exemplary embodiment of the present invention, a polyfunctional acrylate means an acrylate having two or more functional groups in the molecule, and the functional groups may be acrylate groups.
[0046] In one exemplary embodiment of the present invention, the number of functional groups in the polyfunctional acrylate may be 2 or more and 10 or less, preferably 2 or more and 6 or less, and more preferably 2 or more and 5 or less.
[0047] Polyfunctional acrylates can be separately represented as difunctional acrylates with two functional groups and trifunctional acrylates with three functional groups.
[0048] In one exemplary embodiment of the present invention, representative examples of difunctional acrylates may include alkylene glycol di(meth)acrylates, polyoxyalkylene glycol di(meth)acrylates, di(meth)acrylates of halogen-substituted alkylene glycols, di(meth)acrylates of aliphatic polyols, di(meth)acrylates of hydrogenated dicyclopentadiene or tricyclodecanediol, and di... Alkanediol or dialkyldiol Di(meth)acrylates of alkyldialkyl alcohols, di(meth)acrylates of epoxide adducts of bisphenol A or bisphenol F, and epoxy di(meth)acrylates of bisphenol A or bisphenol F, etc.
[0049] In one exemplary embodiment of the present invention, more specific examples of bifunctional acrylates include ethylene glycol di(meth)acrylate, 1,3-butanediol (meth)acrylate, 1,4-butanediol (meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, bis(trimethylolpropane di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate. (Meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, di(meth)acrylate of neopentyl hydroxypentanoate, 2,2-bis[4-{2-(2-(meth)acryloyloxyethoxy)ethoxy}phenyl]propane, 2,2-bis[4-{2-(2-(meth)acryloyloxyethoxy)ethoxy}cyclohexyl]propane, hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, 1,3-di Alkyl-2,5-diyldi(meth)acrylate [Nickname: di] Di(meth)acrylate of alkyl diol di(meth)acrylate, hydroxyneopental and trimethylolpropane acetal product di(meth)acrylate [Chemical name: 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dimethylolpropane] [Alkane], di(meth)acrylate of 1,3,5-tris(2-hydroxyethyl)isocyanurate, etc.
[0050] In one exemplary embodiment of the present invention, a representative example of a polyfunctional acrylate having at least three functional groups is a poly(meth)acrylate of at least a trivalent aliphatic polyol. Specific examples include glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, bis(trimethylolpropane)tri(meth)acrylate, bis(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerol ethylene oxide modified tri(meth)acrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, etc.
[0051] Meanwhile, acrylate oligomers include urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, etc.
[0052] In one exemplary embodiment of the present invention, the polyfunctional acrylate may be neopentyl glycol diacrylate; or tri(2-hydroxyethyl) isocyanurate triacrylate.
[0053] In one exemplary embodiment of the present invention, two types of polyfunctional acrylates may be used.
[0054] In one exemplary embodiment of the invention, a UV-curable adhesive composition is provided, wherein the multifunctional acrylate comprises an acrylate having two functional groups and an acrylate having three or more functional groups, and based on 100 parts by weight of the multifunctional acrylate, it comprises 70 parts by weight or more of an acrylate having two functional groups.
[0055] In another exemplary embodiment of the invention, the polyfunctional acrylate comprises an acrylate having two functional groups and an acrylate having three or more functional groups, and based on 100 parts by weight of the polyfunctional acrylate, it may comprise an acrylate having two functional groups in an amount of 70 parts by weight or more, preferably 70.5 parts by weight or more, more preferably 71 parts by weight or more, and 90 parts by weight or less, preferably 85 parts by weight or less, more preferably 80 parts by weight or less, and most preferably less than 80 parts by weight.
[0056] In another exemplary embodiment, the multifunctional acrylate comprises an acrylate having two functional groups and an acrylate having three or more functional groups, and based on 100 parts by weight of the multifunctional acrylate, it may contain 70 or more and 80 or fewer parts by weight of an acrylate having two functional groups.
[0057] In one exemplary embodiment of the invention, a UV-curable adhesive composition is provided, wherein the acrylate having two functional groups comprises a hydroxypentanoic acid group.
[0058] The multifunctional acrylate contained in the UV-curable adhesive composition according to the present invention comprises two types of acrylates, the acrylate having two functional groups comprising the stated content and specific functional groups, thus improving the wetting properties of the polarizer or substrate and exhibiting excellent adhesive strength regardless of the protective substrate used.
[0059] In one exemplary embodiment of the present invention, the monomer may comprise monofunctional acrylates; polyfunctional acrylates; and silane coupling agents, and may also comprise other additives.
[0060] In one exemplary embodiment of the invention, a UV-curable adhesive composition is provided comprising: based on 100 parts by weight of a monomer, 1 part by weight or more and 30 parts by weight or less of a monofunctional acrylate, and 40 parts by weight or more and 90 parts by weight or less of a polyfunctional acrylate.
[0061] In another embodiment of the invention, based on 100 parts by weight of monomer, the monofunctional acrylate may be 1 part by weight or more and 30 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, more preferably 10 parts by weight or more and 30 parts by weight or less.
[0062] In yet another exemplary embodiment, based on 100 parts by weight of monomer, the polyfunctional acrylate may be 40 parts by weight or more and 90 parts by weight or less, preferably 45 parts by weight or more and 90 parts by weight or less, more preferably 45 parts by weight or more and 85 parts by weight or less.
[0063] Therefore, since monofunctional and polyfunctional acrylates are included in the UV-curable adhesive composition within the aforementioned range, even when a moisture-permeable substrate or an impermeable substrate is stacked on both surfaces of a polarizing plate, it is characterized by having excellent adhesive strength without deterioration of adhesive strength, and also having excellent substrate wetting properties in the adhesive composition after moisture penetration.
[0064] In one exemplary embodiment of the present invention, the UV-curable adhesive composition may contain a silane coupling agent.
[0065] In one exemplary embodiment of the present invention, the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups can be an alicyclic epoxy group or a non-alicyclic epoxy group.
[0066] In another exemplary embodiment of the invention, the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups can be an alicyclic epoxy group.
[0067] In yet another exemplary embodiment of the invention, the silane coupling agent has one or more epoxy groups in the molecule, and at least one of the epoxy groups may be a non-alicyclic epoxy group.
[0068] In yet another exemplary embodiment, the silane coupling agent has an epoxy group in the molecule, and the epoxy group can be a non-alicyclic epoxy group.
[0069] In yet another exemplary embodiment, the silane coupling agent has an epoxy group in the molecule, and the epoxy group can be an alicyclic epoxy group.
[0070] In particular, in an exemplary embodiment of the invention, the silane coupling agent has an epoxy group in the molecule, and when the epoxy group is a non-alicyclic epoxy group, the adhesive properties are not significantly different compared to the case with an alicyclic epoxy group, but can have very superior properties in the initial feasibility assessment compared to the case with an alicyclic epoxy group.
[0071] In one exemplary embodiment of the present invention, the silane coupling agent is not limited to this; any silane coupling agent having an epoxy group can be used, but specifically 3-glycidoxypropyltrimethoxysilane.
[0072] The present invention is characterized in that the UV-curable adhesive composition comprises a silane coupling agent having at least one epoxy group, and in particular, comprises 15 parts by weight or more of the silane coupling agent based on 100 parts by weight of monomer.
[0073] In another exemplary embodiment, based on 100 parts by weight of the monomer, the silane coupling agent may be included in an amount of 15 parts by weight or more, 50 parts by weight or less, preferably 45 parts by weight or less, more preferably 35 parts by weight or less, and most preferably 30 parts by weight or less.
[0074] In this invention, the key feature of the UV-curable adhesive composition is that a silane coupling agent having at least one epoxy group is included in the stated amount, while polyfunctional acrylates and monofunctional acrylates are included in a specific amount, such that they are included in a large amount compared to when applied as an additive to a commonly used adhesive layer.
[0075] In addition to the general function of coupling agents, the silane coupling agent according to the invention is also used as an additive to improve the adhesive strength of the composition, and it has been confirmed that, based on 100 parts by weight of monomer, the silane coupling agent is included in an amount of at least 15 parts by weight or more to have a good effect on the adhesive layer according to the invention.
[0076] That is, since the silane coupling agent according to the present invention contains the stated amount, the adhesion strength is excellent even when various types of protective substrates, such as moisture-permeable / impermeable, moisture-permeable / moisture-permeable and impermeable / impermeable, are used on the upper and lower parts of the polarizing plate, and the wetting properties of the polarizing plate are excellent, thus resulting in an excellent appearance of the polarizing film.
[0077] In one exemplary embodiment of the present invention, the UV-curable adhesive composition may include a cationic initiator and a photosensitizer.
[0078] In this invention, the cationic initiator can be any cationic initiator that can initiate the polymerization of polymerizable monomers and polymerizable polyfunctional acrylates by ultraviolet light irradiation, and conventionally known cationic initiators can be used. Specific examples of photoradical polymerization initiators include acetophenone-based initiators, such as acetophenone, 3-methylacetophenone, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylprop-1-one, 2-methyl-1-[4-(methylthio)phenyl-2-morpholinoprop-1-one and 2-hydroxy-2-methyl-1-phenylprop-1-one; benzophenone-based initiators, such as benzophenone, 4-chlorobenzophenone and 4,4'-diaminobenzophenone; benzoyl ether-based initiators, such as benzoyl propyl ether and benzoyl ethyl ether; thioxanthone-based initiators, such as 4-isopropylthioxanthone; other tonketones, fluorenones, camphorquinone, benzaldehyde and anthraquinones, etc.
[0079] In one exemplary embodiment of the present invention, a cationic initiator refers to a compound that initiates a cationic polymerization reaction by acting on a cationic polymerizable group, such as an epoxy group, or a compound that generates a cationic substance or a Lewis acid by irradiation with active energy rays, such as ultraviolet light.
[0080] In one exemplary embodiment of the present invention, the cationic initiator may include a sulfonium salt or iodine. Salt.
[0081] In one exemplary embodiment of the invention, a cationic initiator is used to increase the curing rate by promoting polymerization, and cationic initiators commonly used in the art can be used without limitation as cationic polymerization initiators.
[0082] Furthermore, in one exemplary embodiment of the invention, mixing photosensitizers can enhance the reactivity of free radical polymerization and improve the mechanical or adhesive strength of the adhesive layer. Photosensitizers can be compounds with maximum absorption at wavelengths greater than 380 nm, and examples include carbonyl compounds, organosulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, anthracene compounds, photoreduction pigments, etc.
[0083] In one exemplary embodiment of the invention, a UV-curable adhesive composition is provided, wherein, based on 100 parts by weight of the UV-curable adhesive composition, a cationic initiator is included in an amount of 0.1 parts by weight or more and 5 parts by weight or less, and a photosensitizer is included in an amount of 0.1 parts by weight or more and 5 parts by weight or less.
[0084] In another embodiment of the invention, based on 100 parts by weight of the UV-curable adhesive composition, the cationic initiator may be included in an amount of 0.1 parts by weight or more and 5 parts by weight or less, preferably 1 part by weight or more and 3 parts by weight or less, more preferably 1.5 parts by weight or more and 2.5 parts by weight or less.
[0085] In another embodiment of the invention, based on 100 parts by weight of the UV-curable adhesive composition, the photosensitizer may be included in an amount of 0.1 parts by weight or more and 5 parts by weight or less, preferably 1 part by weight or more and 3 parts by weight or less, more preferably 1.5 parts by weight or more and 2.5 parts by weight or less.
[0086] Specifically, the UV-curable adhesive composition according to the invention comprises a cationic initiator in the amounts described above, and the invention is characterized by using a free radical monomer as the main material, but using a cationic initiator instead of a free radical initiator. That is, when a free radical initiator is included in the UV-curable adhesive composition according to the invention, as in the invention, neither the moisture-permeable substrate nor the moisture-impermeable substrate has good adhesive strength; instead, the adhesive strength is reduced. The UV-curable adhesive composition according to the invention has a composition that exhibits excellent adhesive strength regardless of the substrate.
[0087] An adhesive film is provided, which contains a UV-curable adhesive composition or a cured product thereof according to the invention.
[0088] The preparation method of the adhesive composition for polarizing plates according to the present invention is not particularly limited, and can be obtained by mixing the components. Organic solvents may also be used appropriately to adjust the viscosity. There are no particular limitations on the mixing method either; the components are thoroughly stirred and mixed in a room shielded from UV light so as not to cure at room temperature (20°C or higher and 25°C or lower) until they become homogeneous in the liquid.
[0089] When applying the adhesive composition to a polarizer, the adhesive composition can be applied to either or both of the transparent protective film and the polarizer.
[0090] During manufacturing, the adhesive film can be stacked on top of the base film.
[0091] In one exemplary embodiment of the invention, the adhesive film may contain, as is, an adhesive composition according to an exemplary embodiment of the invention.
[0092] In one exemplary embodiment of the invention, the adhesive film may comprise a cured product of an adhesive composition according to an exemplary embodiment of the invention.
[0093] In one exemplary embodiment of the present invention, the base film may be selected from polyethylene terephthalate (PET), polyester, polycarbonate (PC), polyimide (PI), polyethylene naphthalate (PEN), polyether ether ketone (PEEK), polyarylate (PAR), polycyclic olefin (PCO), polynorbornene, polyether sulfone (PES), and cyclic olefin polymer (COP).
[0094] In another exemplary embodiment, the base film may be polyethylene terephthalate (PET).
[0095] In one exemplary embodiment of the present invention, the thickness of the base film may be 10 μm or greater and 200 μm or less, preferably 15 μm or greater and 100 μm or less, more preferably 20 μm or greater and 75 μm or less.
[0096] Furthermore, the base film is preferably transparent. Here, "transparent" means that the transmittance of visible light (400 nm to 700 nm) is 80% or greater.
[0097] In one exemplary embodiment of the invention, an adhesive film is provided, the adhesive film further comprising a release film on one or both surfaces of the adhesive film.
[0098] In one exemplary embodiment of the present invention, the thickness of the adhesive film may be 0.1 μm or greater and 300 μm or less.
[0099] In another exemplary embodiment of the present invention, the thickness of the adhesive film may be 0.1 μm or greater and 100 μm or less, 0.1 μm or greater and 80 μm or less, and 0.1 μm or greater and 50 μm or less.
[0100] In one exemplary embodiment of the present invention, the thickness of the adhesive film can be greater than 0 μm and 20 μm or less, greater than 0 μm and 10 μm or less, preferably 0.1 μm to 10 μm, or about 0.1 μm to 5 μm. When the thickness of the adhesive film meets the above ranges, the adhesive film has excellent uniformity and adhesive strength, and can prevent wrinkles on the appearance of the polarizing plate.
[0101] The thickness of the adhesive film is not particularly limited even in the method of applying the solid adhesive composition to the adhesive film solution, and various means can be used, such as direct dripping of the adhesive composition, roller coating, spraying and dipping.
[0102] In one exemplary embodiment of the invention, the adhesive film may have a surface energy of 35 mN / m or less.
[0103] In one exemplary embodiment of the invention, the adhesive film may have a surface water contact angle of 70° or greater.
[0104] In one exemplary embodiment of the present invention, the adhesive film may have a surface energy of 35 mN / m or less, 30 mN / m or less, and 25 mN / m or less, and may meet a surface energy range of 5 mN / m or greater.
[0105] In one exemplary embodiment of the present invention, the adhesive film may have a surface water contact angle of 70° or greater, 100° or greater, and 110° or greater, and may satisfy a surface water contact angle range of 180° or less.
[0106] The adhesive film according to an exemplary embodiment of the present invention satisfies the surface water contact angle and surface energy, and meets the above ranges, because the UV-curable adhesive composition contains monofunctional and polyfunctional acrylates in a specific composition and amount to have excellent wetting properties with the substrate.
[0107] In yet another exemplary embodiment, a polarizing film is provided, comprising: a polarizer; a first adhesive layer and a second adhesive layer disposed on two surfaces of the polarizer; and a layer disposed on the opposite surface of the first adhesive layer to the surface in contact with the polarizer and having a strength of 150 g / m². 2 • A transparent protective film with 24-hour or less moisture permeability; and a surface disposed on the opposite side of the polarizer contact surface of the second adhesive layer, having a moisture permeability of 150 g / m². 2 • A transparent protective film with 24-hour or greater moisture permeability, wherein the first adhesive layer and the second adhesive layer are adhesive films according to the present invention.
[0108] In one exemplary embodiment of the present invention, the polarizing film can be prepared by applying a UV adhesive composition to a polarizer and then bonding the polarizer and a transparent protective film together using a roller laminator or the like.
[0109] Specifically, after bonding, the polarizing plate is irradiated with ultraviolet light to cure the adhesive composition. While there are no particular limitations on the ultraviolet light source, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black lights, microwave-excited mercury lamps, metal halide lamps, etc., with a luminescence distribution at wavelengths of 400 nm or less, can be used. While there are no particular limitations on the ultraviolet irradiation dose (integrated light intensity), it is preferable that the ultraviolet irradiation dose, within the wavelength range that effectively activates the polymerization initiator, is 100 mJ / cm². 2 Or even greater than 2,000 mJ / cm 2Or even less. Within this range, the reaction time is suitable and can prevent deterioration of the adhesive layer itself or the polarizing film due to heat from lamp radiation and heat generated during polymerization.
[0110] The polarizing film is then stored at room temperature (20°C or higher and 25°C or lower, specifically 25°C) for 16 hours or longer and 30 hours or shorter immediately after being irradiated with ultraviolet light. The polarizing film can be prepared by completing the curing process.
[0111] In one exemplary embodiment of the present invention, the transparent protective film material is preferably a material having excellent transparency, mechanical strength, thermal stability, water barrier properties, isotropy, etc. For example, the transparent protective film material may include cellulose resins such as cellulose diacetate and cellulose triacetate; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; acrylic resins such as polymethyl methacrylate (PMMA); polystyrene resins such as polystyrene and acrylonitrile-styrene copolymer (AS resin); polycarbonate resins; polyolefin resins such as polyethylene, polypropylene, ethylene / propylene copolymers, and cyclic olefin polymers, polyvinyl chloride resins; polyamide resins such as nylon or aromatic polyamides; polyimide resins; polysulfone resins; polyethersulfone resins; polyetheretherketone resins; polyphenylene sulfide resins; polyvinyl alcohol resins; polyvinylidene chloride resins; polyvinyl butyral resins; polyaryl ester resins; polyoxymethylene resins; epoxy resins; or blends of these resins, etc.
[0112] In one exemplary embodiment of the present invention, examples of cellulose resins may include cellulose triacetate (TAC), cellulose diacetate, cellulose tripropionate, cellulose dipropionate, etc. Among these, cellulose triacetate, cyclic olefin polymers, polyethylene terephthalate, or acrylic resins are preferred in terms of availability or cost, and cyclic olefin polymers, polyethylene terephthalate, or acrylic resins are more preferred in terms of availability and moisture permeability. If the protective film has high moisture permeability, moisture can easily penetrate the protective film and be introduced to the polarizer side, which may lead to deterioration of the polarizer's quality.
[0113] Polarizers exhibit the property of extracting light vibrating in only one direction from light incident simultaneously vibrating in several directions. This property can be achieved by stretching polyvinyl alcohol (PVA) containing iodine under strong tension. More specifically, for example, a polarizer can be formed by: a swelling step of immersing a PVA film in an aqueous solution to cause it to swell; a step of dyeing the swollen PVA film with a dichroic material that imparts polarization; a stretching step of stretching the dyed PVA film so that the dichroic dye materials are aligned side-by-side in the stretching direction; and a supplementary step of correcting the color of the PVA film after the stretching step. However, the polarizing plate of the present invention is not limited thereto.
[0114] The polarizer can be any polarizer known in the art, such as a film made of polyvinyl alcohol (PVA) containing iodine or dichroic dyes. The polarizer can be manufactured by dyeing the polyvinyl alcohol-based film with iodine or dichroic dyes, but there are no particular limitations on the manufacturing method. The term "polarizing film" refers to a state including both the polarizer and a protective film.
[0115] The polarizer is manufactured by the following steps: uniaxially stretching a polyvinyl alcohol-based resin film; dyeing the polyvinyl alcohol-based resin film with a dichroic dye and adsorbing the dichroic dye; treating the polyvinyl alcohol-based resin film adsorbed with a boric acid aqueous solution; washing the polyvinyl alcohol-based resin film with water after treatment with a boric acid aqueous solution; and bonding a protective film to the uniaxially stretched polyvinyl alcohol-based resin film in which the dichroic dye is adsorbed and oriented through these steps.
[0116] Uniaxial stretching can be performed before, simultaneously with, or after dyeing with dichroic dyes. When uniaxial stretching is performed after dyeing with dichroic dyes, it can also be performed before or during boric acid treatment. Furthermore, uniaxial stretching can be performed in multiple steps. For uniaxial stretching, it can be performed between rollers with different circumferential speeds, or it can be performed using hot rollers. Additionally, uniaxial stretching can be dry stretching in air or wet stretching in a solvent-swelled state. The stretching ratio is not particularly limited, but is typically 4 to 8 times.
[0117] Meanwhile, the thickness of the polarizer is preferably 5 μm to 40 μm, more preferably 5 μm to 25 μm. When the thickness of the polarizer meets the above numerical range, the optical properties are excellent and the amount of polarizer shrinkage at low temperatures is appropriate, thereby exhibiting excellent thermally related durability of the entire polarizing plate.
[0118] Furthermore, when the polarizer is a polyvinyl alcohol-based film, there are no particular limitations on the use of polyvinyl alcohol-based films, as long as the polyvinyl alcohol-based film contains polyvinyl alcohol resin or its derivatives. In this case, polyvinyl alcohol resin derivatives include, but are not limited to, polyvinyl alcohol formaldehyde resin, polyvinyl alcohol acetal resin, etc. Additionally, commercially available polyvinyl alcohol-based films can be used, such as P30, PE30, and PE60 from Kuraray, and M2000, M3000, and M6000 from Nihon Synthetic Co., Ltd., but are not limited to these.
[0119] The degree of polymerization of the polyvinyl alcohol-based film is preferably from 1,000 to 10,000, more preferably from 1,500 to 5,000. When the degree of polymerization meets the above-mentioned numerical range, the molecules move freely and can be flexibly mixed with iodine or dichroic dyes.
[0120] In one exemplary embodiment of the invention, a polarizing film is provided, wherein the adhesive strength of the surface of the first adhesive layer in contact with the polarizer and the surface of the second adhesive layer in contact with the polarizer is 150 gf / inch or greater.
[0121] In another exemplary embodiment of the invention, a polarizing film is provided, wherein the adhesive strength of the surface of the first adhesive layer in contact with the polarizer and the surface of the second adhesive layer in contact with the polarizer is 150 gf / inch or greater, preferably 200 gf / inch or greater and 600 gf / inch or less, more preferably 400 gf / inch or less.
[0122] The unit for adhesive strength is gf / inch, but it can mean the same unit as gf / 20mm or gf / 25mm.
[0123] That is, in the polarizing film according to the invention, a first protective film is used above the polarizer and a second protective film is used below the polarizer. Even when an impermeable substrate is used above and a permeable substrate is used below, the UV-curable adhesive composition has a predetermined composition and content, thereby having excellent adhesive strength as described above.
[0124] Figure 1 A stacked structure of a polarizing film according to an exemplary embodiment of the present invention is shown. Specifically, it can be seen that a first adhesive layer 4 and a second adhesive layer 2 are disposed on two surfaces of the polarizer 3, and moisture permeability of 150 g / m² is disposed above the first adhesive layer 4 and below the second adhesive layer 2, respectively. 2 • Transparent protective film with 24-hour or less protection and a moisture permeability of 150 g / m² 2 • 24-hour or longer transparent protective film 1.
[0125] Figure 1 This is just one example, and the types of protective substrates that can be placed above and below the polarizer are not limited to this.
[0126] In one exemplary embodiment of the invention, a polarizing film is provided in which the first adhesive layer and the second adhesive layer are identical to each other.
[0127] That is, even when both a moisture-permeable substrate and an impermeable substrate are used in the polarizer, unlike existing methods that use different types of adhesives, the polarizing film is characterized by excellent productivity due to the use of the same type of adhesive layer, and the cost increase due to adhesive replacement can be prevented.
[0128] The adhesive composition for polarizing plates according to the present invention can be suitably used in polarizing plates (polarizing films), retardation films, elliptically polarizing films, antireflective films, brightness enhancement films, indium tin oxide sputtered transparent conductive films (ITO films), various electronically related film components or protective films, etc. Even among these, the adhesive composition for polarizing plates is preferably used in polarizing plates (polarizing films).
[0129] Finally, a display device comprising a polarizing film according to the present invention is provided.
[0130] Invention Embodiments
[0131] The invention will be described in detail below by way of embodiments according to the invention and comparative examples not according to the invention, but the scope of the invention is not limited to the following embodiments.
[0132] <Experimental Example>
[0133] UV adhesive compositions having the composition and content shown in Table 1 were prepared respectively.
[0134] Then, the UV adhesive composition was applied to both surfaces of the polarizer (manufactured by Nippon Synthetic Co., Ltd.), and an NRT TAC film (moisture permeability >200 g / m²) from Fuji Co., Ltd. was applied to one surface. 2 • Day) and on the opposite surface, PET from Toyobo Co., Ltd. (moisture permeability <50 g / m²) 2 The layers are stacked and then bonded using a roller laminator.
[0135] Subsequently, ultraviolet light is irradiated onto the polarizing plate to cure the UV adhesive composition. Although there are no particular restrictions on the source of ultraviolet light, light sources with luminous distribution at wavelengths of 400 nm or less, such as low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black lights, microwave-excited mercury lamps, and metal halide lamps, can be used.
[0136] Irradiation with ultraviolet light at a wavelength of 365 nm resulted in an irradiation dose (integrated light intensity) of 2000 mJ / cm². 2The adhesive composition used for the polarizing plate is cured, and then the polarizer and the release protective film are bonded together and cut into dimensions of 2 cm wide × 15 cm long to prepare a polarizing plate sample. At this time, the release protective film is pretreated with KOH relative to each adhesive composition used for the polarizing plate.
[0137] Immediately after irradiation with ultraviolet light, the polarizing film is stored at room temperature (20°C or higher and 25°C or lower, specifically 25°C) for 16 hours or longer and 30 hours or shorter. The polarizing film is obtained by completing the curing process.
[0138] [Table 1]
[0139]
[0140] In Table 1 above, the numbers can refer to the parts by weight contained in the entire adhesive composition (the six types in Table 1). Furthermore, DPGDA:50 in Example 6 means using 50 parts by weight of DPGDA instead of M210. Specifically, the numbers in Table 1 represent the corresponding parts by weight of monomers comprising monofunctional acrylates, polyfunctional acrylates, and silane coupling agents based on 100 parts by weight, and the parts by weight of cationic initiators, photosensitizers, and free radical initiators respectively contained in the entire adhesive composition based on 100 parts by weight.
[0141] At this time, the monomer may also contain other additives, and the content of the additives is not included in Table 1 above.
[0142] In Table 1 above, in order, DPGDA is dipropylene glycol diacrylate, 4-HBA (OSAKA Chemical Co., Ltd.) is 4-hydroxybutyl acrylate, M210 (Miwon Chemical Co., Ltd.) is neopentyl glycol diacrylate of hydroxypentanoic acid, M370 (Miwon Chemical Co., Ltd.) is tri(2-hydroxyethyl)isocyanurate triacrylate, KBM-403 (ShinEtsu Chemical Co., Ltd.) is 3-glycidoxypropyltrimethoxysilane (a material having an epoxy group and at least one non-alicyclic epoxy group), KBM-503 (ShinEtsu Chemical Co., Ltd.) is 3-m-hydroxypropyltrimethoxysilane (a material without an epoxy group), and KBM-5103 (ShinEtsu Chemical Co., Ltd.) is... Co., Ltd. is acryloyloxypropyltrimethoxysilane (a material without an epoxy group), Omnicat 250 is (4-methylphenyl)[4-(2-methylpropyl)phenyl]-hexafluorophosphate (1-) in propylene carbonate, and DETX (IHT Co., Ltd.) is 2,4-diethylthioxanthone.
[0143] The polarizing films prepared above were evaluated in the following experimental examples 1 to 4, and the results are shown in Table 2.
[0144] [Table 2]
[0145]
[0146] <Experimental Example 1: Peel Strength Test of Protective Film>
[0147] Peel off the protective film at a rate of 0.5 cm / s for 3 cm or more, and measure the peel strength three times to calculate the average value. Peel strength was measured using an XT Plus Texture Analyzer (manufactured by TA).
[0148] At this point, the peel strength (gf / 20mm) is evaluated as follows: ◎ for 200gf / 20mm or greater, ○ for 120gf / 20mm or greater but less than 200gf / 20mm, △ for 100gf / 20mm or greater but less than 120gf / 20mm, and X for less than 100gf / 20mm.
[0149] <Experimental Example 2: Evaluation of Thermal Shock Resistance>
[0150] The prepared polarizing film was cut into pieces with lengths of 150 mm in both the absorption axis direction and the direction perpendicular to it. Then, an adhesive was applied to one surface of the release protective film, which was then laminated onto a glass substrate and left to stand at 25°C for 24 hours.
[0151] Subsequently, the glass substrate was placed at -40°C for 30 minutes and then at 85°C for 30 minutes, and this cycle was repeated 100 times. After the thermal shock was applied, the presence of polarizer cracks was observed from the end of the polarizer in the tensile direction of the polarizer. When a polarizer crack was observed, the length of the crack was measured. When multiple cracks were observed, their average value was used to evaluate the thermal shock resistance.
[0152] Thermal shock resistance was assessed as follows: ◎ when there were no cracks or the length of the crack was less than 1 mm, ○ when the length of the crack was about 10 mm, △ when the length of the crack was about 50 mm, and X when there were bundles of linear cracks.
[0153] <Experimental Example 3: Curing Rate>
[0154] Irradiation with ultraviolet light at a wavelength of 365 nm resulted in an irradiation dose (integrated light intensity) of 2000 mJ / cm². 2 The adhesive composition used for polarizing plates is then cured. Immediately after peeling off the protective film, the cured film is rubbed by hand to check for slippage.
[0155] The curing rate was evaluated as follows: ◎ for less than 10 seconds, ○ for more than 10 seconds and less than 20 seconds, △ for more than 20 seconds and less than 50 seconds, and X for more than 50 seconds.
[0156] <Experimental Example 4: Substrate Wetting Properties>
[0157] Secure the protective film (TAC film), then apply the adhesive composition using the #3 stick. After 30 seconds, check for dehumidification on the film surface.
[0158] Excellent wetting properties to the substrate are rated as ◎, while lateral shrinkage and annular desiccation are rated as X.
[0159] As can be seen in Table 2 above, the UV-curable adhesive compositions (Examples 1 to 7) according to exemplary embodiments of the present invention necessarily contain monofunctional acrylates; polyfunctional acrylates; silane coupling agents; cationic initiators; and photosensitizers. In particular, based on 100 parts by weight of the adhesive composition, the silane coupling agent is included in an amount of 15 parts by weight or more, the silane coupling agent having one or more epoxy groups in the molecule, and at least one of the epoxy groups including alicyclic epoxy groups or non-alicyclic epoxy groups, thereby exhibiting excellent adhesive strength regardless of whether the substrate to be attached is moisture-permeable or moisture-impermeable.
[0160] As can be seen in the examples in Table 2 above, Examples 1 to 7, in particular those with non-alicyclic epoxy groups, demonstrated excellent results in the evaluation of peel strength and thermal shock resistance. This is because, in the initial feasibility assessment, the non-alicyclic epoxy groups were superior to those using alicyclic epoxy groups.
[0161] Furthermore, as can be seen in Examples 1 to 7, it can be confirmed that the included multifunctional acrylates include two types of acrylates, and the acrylates having two functional groups contain specific amounts and specific functional groups, thus improving the wetting properties of the polarizing plate or substrate and having excellent adhesive strength regardless of the protective substrate used.
[0162] For reference, Examples 1 to 5 and 7 correspond to the case where the acrylate having two functional groups includes a hydroxyneopentic acid group, while Example 6 corresponds to the case where it does not have a hydroxyneopentic acid group. In this case, subtle differences exist, but differences can be observed in terms of adhesive strength to the TAC(NRT) substrate. That is, it is confirmed that the properties according to the invention are excellent when the acrylate having two functional groups includes a hydroxyneopentic acid group.
[0163] It has been confirmed that the UV-curable adhesive composition according to an exemplary embodiment of the present invention contains monofunctional and polyfunctional acrylates in specific amounts to reduce the surface energy of the adhesive layer containing the composition and has excellent wetting properties to the polarizer or substrate without causing bubbles during the process, thereby having excellent appearance quality of the polarizing film containing the composition.
[0164] Comparative Examples 1 to 4 in Table 2 above correspond to cases that do not contain monofunctional acrylates, polyfunctional acrylates, photosensitizers, or cationic initiators, respectively. The experimental results show that the adhesive strength is poor and the thermal shock resistance is poor.
[0165] Comparative Examples 5 and 6 in Table 2 above contain silane coupling agents but do not have epoxy groups as functional groups, confirming that their peel strength and thermal shock resistance are also poor.
[0166] In addition to the general function of coupling agents, the silane coupling agent according to the present invention is also used as an additive to improve the adhesive strength of the composition. However, in Comparative Examples 7 and 8, which correspond to 100 parts by weight of monomer, the silane coupling agent is included in an amount of less than 15 parts by weight, thus confirming that the adhesive strength is not as good as that of the examples.
[0167] In Comparative Example 9, the acrylate having two functional groups (bifunctional groups) was less than the scope of the invention. In Comparative Example 10, no acrylate having two functional groups (bifunctional groups) was used. In the case of Comparative Example 9, the measured adhesive strength was higher than that of the other comparative examples, but it was confirmed that the adhesive strength was still worse than that of the examples. Furthermore, Comparative Example 10 corresponds to the case containing one type of polyfunctional acrylate. In this case, it was confirmed that, as with the other comparative examples, the evaluation of peel strength and thermal shock resistance was also poor.
Claims
1. A UV-curable adhesive composition comprising: a monofunctional acrylate; a polyfunctional acrylate; a silane coupling agent; a cationic initiator; and a photosensitizer. The monomer comprises, based on 100 parts by weight, the monofunctional acrylate, the polyfunctional acrylate, and the silane coupling agent, wherein the silane coupling agent is included in an amount of 15 parts by weight or more. The polyfunctional acrylates include acrylates having two functional groups and acrylates having three or more functional groups. The polyfunctional acrylate is based on 100 parts by weight, wherein the acrylate having two functional groups is included in an amount of 70 parts by weight or more. The acrylate having two functional groups includes a hydroxypentanoic acid group, and The silane coupling agent has one or more epoxy groups in its molecule, wherein at least one of the epoxy groups is an alicyclic epoxy group or a non-alicyclic epoxy group.
2. The UV-curable adhesive composition of claim 1, wherein based on 100 parts by weight of the monomer, it comprises 1 part by weight or more and 30 parts by weight or less of the monofunctional acrylate, and comprises 40 parts by weight or more and 90 parts by weight or less of the polyfunctional acrylate.
3. The UV-curable adhesive composition of claim 1, wherein, based on 100 parts by weight of the UV-curable adhesive composition, the cationic initiator is included in an amount of 0.1 parts by weight or more and 5 parts by weight or less, and the photosensitizer is included in an amount of 0.1 parts by weight or more and 5 parts by weight or less.
4. The UV-curable adhesive composition according to claim 1, wherein the functional groups of the monofunctional acrylate and the polyfunctional acrylate are acrylate groups.
5. The UV-curable adhesive composition of claim 1, wherein based on 100 parts by weight of the multifunctional acrylate, it comprises 70 parts by weight or more and 80 parts by weight or less of the acrylate having two functional groups.
6. An adhesive film comprising a UV-curable adhesive composition or a cured product thereof according to any one of claims 1 to 5.
7. The adhesive film according to claim 6, further comprising: Release film on one or both surfaces of the adhesive film.
8. The adhesive film of claim 6, wherein the thickness of the adhesive film is 0.1 μm or greater and 300 μm or less.
9. A polarizing film, comprising: Polarizer; A first adhesive layer and a second adhesive layer are disposed on the two surfaces of the polarizer; It is disposed on the opposite surface of the first adhesive layer that contacts the polarizer and has a density of 150 g / m. 2 • A transparent protective film with 24-hour or less moisture permeability; as well as It is disposed on the opposite surface of the second adhesive layer that contacts the polarizer and has a density of 150 g / m. 2 • A transparent protective film with 24-hour or longer moisture permeability The first adhesive layer and the second adhesive layer are adhesive films according to claim 6.
10. The polarizing film of claim 9, wherein the adhesive strength of the surface of the first adhesive layer in contact with the polarizer and the surface of the second adhesive layer in contact with the polarizer is 150 gf / inch or greater.
11. The polarizing film of claim 9, wherein the first adhesive layer and the second adhesive layer are identical to each other.
12. A display device comprising the polarizing film according to claim 9.
Citation Information
Patent Citations
rechargeable battery cells
KR1020210151166A
Active energy ray-polymerizable adhesive and laminate
JP2018168213A
